(untitled) (المجلة الدولية للبحوث العلمية, 2026)
Developing a planning vision for establishing a sustainable transport system in Al-Hilla City represents one of the most significant factors contributing to the vitality and dynamism of the urban framework. Such a system provides comfort and quality for urban residents and serves as an effective tool for intervention and influence within the city. Given its importance, sustainable transport has become a key instrument of sustainability worldwide, aiming primarily at urban regeneration, enhancing the city’s modern image, preserving its environment, and acting as the backbone that connects its neighborhoods. Accordingly, this project falls within the framework of the urban development strategy and the Sustainable Transport Plan of Babil Governorate. Al-Hilla City is considered a central area and an important transportation node, characterized by continuous urban and population growth, which has negatively affected traffic movement and the development of the transport network. This situation prompted to study the impact of the tramway system on achieving a sustainable urban environment in Al-Hilla and to incorporate the tramway project within the governorate’s strategic plans. The study examined the role of the tramway in urban regeneration based on several field studies and analytical outputs, concluding that certain areas should be prioritized for tramway corridors while ensuring integration among them. The research findings indicate that the lack of comfortable public transport modes and the inadequate provision of stations and bus services have led to road networks being unable to accommodate private vehicles, particularly in university districts and along major arterial streets. Furthermore, insufficient accessibility within neighborhoods has resulted in difficulties in reaching many urban areas. Based on these findings, the tramway was proposed as an effective solution to improve the urban environment and revitalize the urban dynamism of Al-Hilla City. This was achieved through proposing three alternative tramway network routes and selecting the optimal option with the least conflicts while serving the largest proportion of the city’s population.